Kiki: A Chatbot Application For OCD In Android Mobile Application - Kong, Kei (2023)
Many people experience mental health problems. However, if persistent symptoms or signs cause frequent stress and interfere with your performance, it becomes a mental illness. There are many common mental illnesses but, in this project, we will focus on one of the common mental illnesses which is obsessive-compulsive disorder (OCD). Obsessive-compulsive disorder (OCD) is a mental illness that causes repeated unwanted thoughts or sensations (obsessions) or the urge to do something over and over again (compulsions). Some people can have both the obsession and compulsions. In this project, I will propose a chatbot mobile application that focus on OCD that is free to download and no need to purchase for premium version to get all the features. This is because after studying the three existing system, most of the system are for general mental illness and need to purchase for the premium version to use their features. The features in the proposed system are chatbot, self-test, extra information and diary. The proposed system implements agile development methodology that consist of six phases which are requirement gathering and planning, design, development, integration and testing, deployment and review phases. The user acceptance testing (UAT) is conducted in order to identify the error or to determine whether the system meets the requirements. Then the system will be released and feedback are collected from the user.